A Clinicopathological Study of 29 Spitzoid Melanocytic Lesions With ALK Fusions, Including Novel Fusion Variants, Accompanied by Fluorescence In Situ Hybridization Analysis for Chromosomal Copy Number Changes, and Both TERT Promoter and Next-Generation Sequencing Mutation Analysis. (August 2020) - Kastnerova, Liubov; Martinek, Petr; Grossmann, Petr; Steiner, Petr; Vanecek, Tomas; Kyclova, Jitka; Ferak, Ivan; Zalud, Radim; Slehobr, Ondrej; Svajdler, Peter; Sulc, Miroslav; Bradamante, Mirna; et al.
Abstract : ALK-fused spitzoid neoplasms represent a distinctive group of melanocytic lesions. To date, few studies addressed genetic and chromosomal alterations in these lesions beyond the ALK rearrangements. Our objective was to study genetic alterations, including ALK gene fusions, telomerase reverse transcriptase promoter ( TERT -p) mutations, chromosomal copy number changes, and mutations in other genes. We investigated 29 cases of Spitz lesions (11 Spitz nevi and 18 atypical Spitz tumors), all of which were ALK immunopositive. There were 16 female and 13 male patients, with age ranging from 1 to 43 years (mean, 18.4 years). The most common location was the lower extremity. Microscopically, all neoplasms were polypoid or dome shaped with a plexiform, predominantly dermally located proliferation of fusiform to spindled melanocytes with mild to moderate pleomorphism. The break-apart test for ALK was positive in 17 of 19 studied cases. ALK fusions were detected in 23 of 26 analyzable cases by Archer FusionPlex Solid Tumor Kit. In addition to the previously described rearrangements, 3 novel fusions, namely, KANK1-ALK, MYO5A-ALK, and EEF2-ALK, were found. Fluorescence in situ hybridization for copy number changes yielded one case with the loss of RREB1 among 21 studied cases. TERT -p hotspot mutation was found in 1 of 23 lesions. The mutation analysis of 271 cancer-related genes using Human Comprehensive Cancer Panel was performed in 4 cases and identified in each case mutations in several genes with unknown significance, except for a pathogenic variant in the BLM gene. Our study confirms that most ALK fusion spitzoid neoplasms can be classified as atypical Spitz tumors, which occurs in young patients with acral predilection and extends the spectrum of ALK fusions in spitzoid lesions, including 3 hitherto unreported fusions. TERT -p mutations and chromosomal copy number changes involving 6p25 ( RRB1 ), 11q13 ( CCND1 ), 6p23 ( MYB ), 9p21 ( CDKN2A ), and 8q24 ( MYC ) are rare in these lesions. The significance of mutation in other genes remains unknown.